2019
DOI: 10.1111/soc4.12740
|View full text |Cite
|
Sign up to set email alerts
|

After coming out: Parental acceptance of young lesbian and gay people

Abstract: This study examines extant scholarly knowledge on parental acceptance of young lesbian and gay people in traditional heteronormative families. Recent literature shows that parents generally accept their lesbian and gay children. However, parents do not always accept them immediately after they come out. Acceptance takes time, and transitioning to acceptance is often a complex process that depends on parents' access to the necessary resources for coping with the stresses of knowing that their child identifies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 70 publications
(233 reference statements)
0
11
0
Order By: Relevance
“…Therefore, it makes sense to focus on parents' role in the development and performance of children's heterosexuality. For an excellent recent review on how parents respond to and contend with children's nonheterosexuality, see Ghosh (2020). However, I do draw on some literature about children's nonheterosexuality when necessary.…”
mentioning
confidence: 99%
“…Therefore, it makes sense to focus on parents' role in the development and performance of children's heterosexuality. For an excellent recent review on how parents respond to and contend with children's nonheterosexuality, see Ghosh (2020). However, I do draw on some literature about children's nonheterosexuality when necessary.…”
mentioning
confidence: 99%
“…Qualitative and quantitative studies reveal that positive family relationships and family acceptance are protective factors for racially diverse SMY and associated with increased well-being into adulthood (Katz-Wise et al, 2016;Lawson et al, 2019). Parent-child relationships following disclosure tend to get better over time, even if the initial reactions were negative (Ghosh, 2019). In a longitudinal, multi-wave study of 232 racially diverse LGBT adolescents, McConnell et al (2016) found that SMY who reported no family support at time one reported a significant increase in family support over time.…”
Section: Parent-child Relationship Qualitymentioning
confidence: 99%
“…By recruiting multiple family members for studies on this topic, researchers can address how systems of relationships between parents, adolescents, siblings, and extended family members socialize adolescents. For example, research on SMY identity disclosure indicates that SMY are more likely to first disclose to their mother rather than their father and less likely to report disclosing to their father than their mothers during adolescence (e.g., Ghosh, 2019;Katz-Wise et al, 2016). How does disclosure influence who is responsible for communicating about sex with SMY adolescents?…”
Section: Conclusion and Considerations: Toward A More Inclusive Futurementioning
confidence: 99%
“…Taking this Franco-Latin standpoint, Laguna (2016) indicates that in using this term we refer to the dichotomy between heteroparental and same-sex, giving the impression that one of the classifications (heteroparental) is considered to be superior to the other, given that it is linked to social reproduction. From this conception, the term could serve to present census data, without understanding the complex diversity that can be found amongst gay fathers and lesbian mothers ( Farr et al., 2019 ; Ghosh, 2019 ; Watson et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%